Hybrid teaching at the Algerian University: Between challenges, obstacles and perspectives - BOUSSEBAT, Omar (Journal of Human Sciences, 2025)
In this contribution, we discuss hybrid teaching in Algerian higher education institutions. This mode, imposed by the Covid- 19 pandemic, is implemented to protect teaching staff and students from contamination and to validate the academic year. The shift from traditional teaching, which consists of exclusively delivering lectures and tutorials in person, to hybrid teaching, which results from « a combination of learning activities offered in person, in real times, and remotely, in synchronous and asynchronous times » (ENDRIZZI, L. 2012 : 14), was not a sinecure at it poses problems for both teachers and students. Regarding the adopted methodology,we conducted a survey within the Department of Letters and French Language, at the Frères MENTOURI- Constantine 1 University. Starting from the idea that the questionnaire is the basic tool of the survey, we relied on two questionnaires, the first is intended for our French colleagues, the second is addressed to second- year Master’s students, option Language Sciences. The responses from our informants allowed us to confirm two hypotheses, the first is related to the difficulties that the disance teaching mode poses to teachers, the second concerns the problems that students face.